Constituição de si e formação docente: reflexões (auto)biográficas de professores - Silva, Iara Batista da (2023)
The meaning we give to the exercise of teaching requires that the teacher seek elements in their training that allow them to understand themselves in the profession and in the training process. With the objective of contributing to the self-education of teachers from the understanding of the constitution of their teaching, we start from the following research problem: How to promote the self-education of teachers from the understanding of how they constituted themselves as teachers? The fabric of the dialogue is based on considerations about ipseity and teacher training imbricated in the epistemology of research-training, through the (auto)biographical approach, considering that the life stories of teachers are fruitful sources in research in education. The research is guided by the narrative approach, as we agree that it enables the writing and reflection of the experiences arising from the intrinsic daily life in the pedagogical practice. For the construction of the data, we used the training memorial and the narrative interview, as they allow the turning to oneself and the emergence of the subjectivities imbued in the training/self-training. The research participants were two groups of teachers, the first being composed of three teachers of the English language, and the second by teachers who participated in the Pedagogical Workshop entitled: Constitution of the self and the teacher's office: biographical reflections and teacher training, elaborated as an educational product of the present research. The development of this study showed that the fecundity of research-training for understanding the constitution that, in the role of the reflective teacher, re-signifies the process of construction/deconstruction/reconstruction of teaching, rebuilds their teaching identity and becomes aware of their personal and professional actions. establishing, therefore, new knowledge and behaviors that will contribute for the teacher to develop their ability to create, innovate and organize their ideas and methodologies, among other practices of the profession's craft.